Calcaneotalotibial arthrodesis by retrograde intramedullary nailing using expert tibia nail for charcot osteoneuropathy of the foot: A case series - Oesman, I. (Int J Surg Case Rep, 2019)
INTRODUCTION: Charcot osteoneuroarthopathy (CN) is a progressive degenerative arthropathy determined by the interaction of neuropathy, osteopaenia and proinflammatory cytokines. The aim of treatment is to maintain the foot on plantigrade position, recover foot deformity, osseous stability, and prevent ulceration. Intramedullary fixation in calcaneotalotibial arthrodesis has been described in promotion of rigid internal fixation with minimal soft tissue violation producing deformity correction, minimal periosteal aggression, vascular damaged and good functional outcome, with less postoperative fusion time and able to achieve fusion of the ankle and the subtalar joint after failed fusion. PRESENTATION OF CASE: Two patients with charcot foot underwent tibiocalcaneal arthrodesis with retrograde intramedullary technique by Expert Tibial Nail (ETN). The patients are both male 59 years with right ankle deformity 9 months prior to admission and history of trauma and 40 years old with history of Type 2 Diabetes Mellitus. Visual analog scale (VAS), AOFAS and SF score were assessed pre and post operative. DISCUSSION: A good stability, plantigrade ankle and painless foot on both patients were achieved with a mean score 9 for satisfaction. Pre and 3 months post operative VAS were 4 and 1, AOFAS Scale were 58 and 83, mean of SF-36 were 28.4 and 48.6 for physical condition, 37.3 and 67.2. for mental condition consecutively. No severe postoperative complication were recorded CONCLUSION: Tibiotalocalcaneal arthrodesis with retrograde intramedullary technique using ETN system was proven to have a good option for ankle joint salvage with improvement of clinical and functional score. Hence, its application in the charcot joint is promising.